The Role of Professionalism, Auditor’s Experience, and Independence in Improving the Quality of Audit Results: Empirical Study on The Government Internal Monitoring Apparatus ITJEN Kemendikbudristek - Prasetya, Budi Agung; Purwana, Dedi; Muhtar, Saparuddin (Journal of Ecohumanism, 2024)
The Government Internal Monitoring Apparatus is an important part of government management to realize good governance. This research aims to carry out analysis through the stages of identifying, reviewing, and proving hypotheses, as well as finding variables that influence the quality of audit results. The research method used is a mixed parallel convergent method. This research analyzes data through two analyses: quantitative and qualitative analysis, quantitative data was collected through questionnaires from 201 ITJEN Kemendikbudristek auditors. while qualitative data was obtained through interviews and observation. The analysis technique uses SPSS 26.0, Amos 5, and QSR NVivo 20.2 software. Research results from the quantitative analysis show that the level of professionalism, experience, independence, and quality of audit results at ITJEN Kemendikbudristek is in the sufficient category. The causal relationship between professionalism, experience, independence, and the quality of audit results is not significantly strengthened by the existence of the working time moderating variable. The model with the moderating variable produces a fit model. Likewise, the proposed model without the moderating variable produces a fit model. A model that can not only interpret samples but also interpret the population as a whole. The model without the moderating variable has a much more effective model, namely 15.2%, compared to the model with working time with a model effectiveness level of 15.1%. The research results from the qualitative analysis show that the level of professionalism, experience, independence, and quality of audit results at ITJEN Kemendikbudristek is in the sufficient category. These results are in line with the results of quantitative analysis using arithmetic average calculations. For this reason, increasing the professionalism, experience, and independence of auditors, which is currently considered sufficient, will further improve the quality of audit results when the level of professionalism, experience, and independence increases.